2020
DOI: 10.1080/00220388.2020.1715941
|View full text |Cite
|
Sign up to set email alerts
|

Can Wage Subsidies Boost Employment in the Wake of an Economic Crisis? Evidence from Mexico

Miriam Bruhn

Abstract: The rise in unemployment during an economic crisis poses a significant concern to policy makers. This paper measures the effect of a program in Mexico that granted firms in certain industries wage subsidies if they decided to keep their workers instead of letting them go during the recent economic crisis. The analysis uses monthly administrative data on employment at the industry level, along with propensity score matching to construct groups of eligible and ineligible durable goods manufacturing industries th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Among these factors, prior studies suggest that access to government support plays an important role. For instance, short-term government support has been shown to speed up economic recovery, especially for SMEs (Bruhn, 2020;De Mel et al, 2012). Initial studies of the Paycheck Protection Program in the United States showed that receiving grants was associated with increased employment and business survival, but allocation of these grants was skewed towards larger firms (Humphries et al, 2020).…”
Section: Related Literature: Systemic Shocks and Firmsmentioning
confidence: 99%
“…Among these factors, prior studies suggest that access to government support plays an important role. For instance, short-term government support has been shown to speed up economic recovery, especially for SMEs (Bruhn, 2020;De Mel et al, 2012). Initial studies of the Paycheck Protection Program in the United States showed that receiving grants was associated with increased employment and business survival, but allocation of these grants was skewed towards larger firms (Humphries et al, 2020).…”
Section: Related Literature: Systemic Shocks and Firmsmentioning
confidence: 99%
“…The recent economic crisis and the present Corona Virus Disease (COVID-19) pandemic-related economic lockdowns have had worrying effects on jobs and working lives (Doran & Fingleton, 2016;Spurk & Straub, 2020). Such situations in addition to the surge in youth populations in some parts of the world have facilitated an increase not only in the number of people in unemployment (Ackah-Baidoo, 2016;Awad, 2019;Bruhn, 2020;Liotti, 2020;Wilkinson et al, 2017) but also those in insecure and precarious employment (Gutiérrez-Barbarrusa, 2016;Kottwitz et al, 2017;Ståhl & MacEachen, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Corporate solvency problems arising after the lockdown generated systemic risks of bankruptcies in cascade, which could be transmitted through the disturbance of the financial system and value chains. Administrative burdens and delays in the reimbursement of the subsidies may slow down the flow of necessary liquidities to pay workers and generate an adverse impact on lay‐offs for companies using STW first and foremost to deal with cash flow problems (Bruhn, 2020). The rapidity of administration of JobKeeper applications and the efficient governance of the policy are core parameters that impacted its efficiency in the short run.…”
Section: Policy Parameters Of Jobkeepermentioning
confidence: 99%
“…Up to now, empirical evaluations of STW programs have analysed their impact mainly on three dimensions: labour market outcomes in terms of employment rate, wages, labour hoarding and lay‐offs (Boeri & Bruecker, 2011; Bruhn, 2020; Hijzen & Venn, 2011; Nevoux, 2018; OECD, 2020a); firms dynamics in terms of bankruptcies, survival or exit of firms (Calavrezo et al., 2010); working time reorganisations through work‐sharing practices (Duhautois et al., 2009). …”
Section: Measuring the Effects Of Jr Programsmentioning
confidence: 99%
See 1 more Smart Citation